2.1.72 \(u_t + x u_x = 0\) with \(u(x,0)=x^2\). Math 5587

problem number 72

Added May 23, 2019.

From Math 5587 midterm I, Fall 2016, practice exam, problem 3.

Solve for \(u(x,t)\) \begin {align*} u_t + x u_x = 0 \end {align*}

With with \(u(x,0)=x^2\)

Mathematica


\[\left \{\left \{u(x,t)\to e^{-2 t} x^2\right \}\right \}\]

Maple


\[u \left (x , t\right ) = x^{2} {\mathrm e}^{-2 t}\]

Hand solution

Solve \(u_{t}+xu_{x}=0\) with \(u\left ( x,0\right ) =x^{2}\). Using the method of characteristics, the systems of characteristic lines are (from the PDE itself)\begin {align} \frac {dt}{ds} & =1\tag {1}\\ \frac {dx}{ds} & =x\tag {2}\\ \frac {du}{ds} & =0\tag {3} \end {align}

With initial conditions at \(s=0\)\[ t\left ( 0\right ) =0,x\left ( 0\right ) =\xi ,u\left ( 0\right ) =\xi ^{2}\] Equation (1) gives\begin {align} t & =s+t\left ( 0\right ) \nonumber \\ & =s\tag {5} \end {align}

Equation (2) gives\begin {align} \ln x & =s+x\left ( 0\right ) \nonumber \\ x & =\xi e^{s}\tag {6} \end {align}

From (5,6) solving for \(\xi \) gives\begin {align} \xi & =xe^{-s}\nonumber \\ & =xe^{-t}\tag {7} \end {align}

Equation (3) gives\begin {align*} u & =u\left ( 0\right ) \\ & =\xi ^{2}\\ & =x^{2}e^{-2t} \end {align*}

________________________________________________________________________________________